Adoption of Improved Chickpea Production Package in East Shoa, Ethiopia - Almaz Ciziew; Ranjan S. Karippai; Teklu Tesfaye (Journal of Agricultural Extension Management, 2025)
Chickpea is one of the major pulse crops grown in Ethiopia. It plays an important role in improving household income, nutrition and food security. Despite its high production potential in Eastern Shoa in general and the study districts in particular, chickpea growers did not benefit from chickpea production. Low production, which is mainly associated with non-adoption and unwillingness of farmers to adopt the recommended chickpea production package were among the major problems. The objective of this study was to identify factors influencing adoption and intensity of adoption of chickpea technology package in Ada’a and Akaki districts. Results of the econometric (Tobit) model indicated that sex of household head, land holding, social participation, attitude towards chickpea technology package and innovation proneness were found to have positive and significant influence on adoption and intensity of adoption of improved chickpea production package. On the other hand, experience in chickpea cultivation had shown negative and significant relationship with adoption and intensity of adoption of improved chickpea production package. Female-headed households could nor- adopt chickpea technology. This might -be due to lack of access to information sources. Accordingly, opportunities for equal access for women farmers should be provided through provision of empowerment intervention.